1,130 GRADUATES RECEIVE THEIR DEGREES AT USM 51st CONVOCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 27 April 2015 A total of 1,130 graduates received their degrees at the Universiti Sains Malaysia (USM) 51 Convocation Ceremony held in three sessions at the Dewan Tuanku Syed Putra (DTSP) here, which ended last Sunday.